Resistance of transgenic papaya trees to papaya ringspot in Brazil - Meissner Filho, Paulo Ernesto; Vilarinhos, Alberto Duarte; Oliveira, Vania Jesus dos Santos de; Silva, Dreid de Cerqueira Silveira da; Santos, Vanderlei da Silva; Dantas, Jorge Luiz Loyola (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to evaluate the resistance of transgenic papaya populations (PTPs) to Papaya ringspot virus-P (PRSV-P). 'Sunrise Solo' transgenic papaya plants were produced with the gene of the PRSV-P protein coat, and PRSV was mechanically inoculated in plants in greenhouse conditions. The presence of the CP/PRSV gene and homozygosis were evaluated by polymerase chain reaction (PCR). Selected plants and the 'Sunrise Solo' control were transplanted to the field for agronomic evaluations. The plants evaluated in greenhouse conditions showed resistance between 96.3 and 5.8%, without variation of symptoms. The PTPs 1/6, 1/7, 1/9, 1/10, 1/15, 2/38, 2/41, 2/56, 2/65, 3/27, 3/46, 3/48, 4/9, 4/27, 8/4, 8/23, 8/33, 18/3, 18/4, 18/8, 18/22, 18/27, 28/97, 28/104, and 28/110 showed no symptoms, they were ELISA negative, and most of them contained the CP and NPT II genes. PTPs 1/6 and 3/46 had the CP gene in homozygosis and in double insertion. PTPs 1/6/20, 1/6/59, 1/6/64, 1/6/90, 3/46/44, 3/46/52, and 18/27/97 had a well-formed fruit cluster, piriform fruit weighing approximately 500 grams, orange pulp, and less than 10% carpelloidy. PTPs 1/6/59 and 3/46/52 show resistance to PRSV, good agronomic characteristics, and the CP gene in homozygosis.